Rates of Insurance for Injured Patients Before and After Health Care Reform in Massachusetts: A Possible Case of Double Jeopardy - Santry, Heena P. (American Public Health Association, 2014)
Objectives. We determined how preinjury insurance status and injury-related outcomes among able-bodied, community-dwelling adults treated at a Level I Trauma Center in central Massachusetts changed after health care reform. Methods. We compared insurance status at time of injury among non-Medicare-eligible adult Massachusetts residents before (2004–2005) and after (2009–2010) health care reform, adjusted for demographic and injury covariates, and modeled associations between insurance status and trauma outcomes. Results. Among 2148 patients before health care reform and 2477 patients after health care reform, insurance rates increased from 77% to 84% (P < .001). Younger patients, men, minorities, and penetrating trauma victims were less likely to be insured irrespective of time period. Uninsured patients were more likely to be discharged home without services (adjusted odds ratio = 3.46; 95% confidence interval = 2.65, 4.52) compared with insured patients. Conclusions. Preinjury insurance rates increased for trauma patients after health care reform but remained lower than in the general population. Certain Americans may be in “double jeopardy” of both higher injury incidence and worse outcomes because socioeconomic factors placing them at risk for injury also present barriers to compliance with an individual insurance mandate.